Aplikasi Eco Enzyme Limbah Kulit Pisang Dan Model Budidaya Pada Pertumbuhan Dan Hasil Tanaman Jagung Ketan (Zea mays Cerantina) Lokal Dompu - azhar azhar (AGRONISMA, 2021)
Corn is a cereal commodity that has a role as the second fulfillment of carbohydrate needs after rice. Glutinous corn (Zea mays C) is a type of corn that has a special character, which contains almost 100% levels of amylopectin and is used fresh or processed as local food which is a regional specialty in Indonesia. Eco enzyme is an enzyme produced from the fermentation process of natural ingredients, such as plant proteins, minerals and hormones. This study aims to determine the effect of eco enzyme and cultivation model on the growth of local glutinous corn, to determine the effect of eco enzyme and cultivation model on the yield of local corn glutinous rice, and to determine the effect of eco enzyme and cultivation model on growth and yield of local maize. The experimental design used in this study was a factorial randomized block design (RAK) with a control consisting of two factors. The first factor is the application of Eco enzyme (E), which consists of three levels E1 = 1% (10 ml), E2 = 1.5% (15 ml) and E3 = 2% (20 ml). The second factor is the cultivation model (M), which consists of three levels M1 = Minimum Tillage, M2 = Organic and M3 = Inorganic plus the control treatment. The results showed that the application of eco enzyme with a cultivation model had no effect on the growth of glutinous corn plants but did affect the yield of glutinous corn plants. The application of eco-enzyme combined with a cultivation model using organic goat manure gave maximum results at cob weight without cob 104.36 (g), cob length 13.33 (g), ear diameter 40.37 (g) and cob seed weight 80, 59 (g).